Colchicine to Prevent Periprocedural Myocardial Injury in Percutaneous Coronary Intervention: The COPE-PCI Pilot Trial. (19th May 2021) - Cole, Justin; Htun, Nay; Lew, Robert; Freilich, Mark; Quinn, Stephen; Layland, Jamie
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Periprocedural myocardial infarction and injury (PM-injury) are the most common complications of percutaneous coronary intervention (PCI) and are associated with future adverse cardiac events. Inflammation plays a pivotal role in the development of PM-injury. In this randomized pilot trial, we assessed the effect of an anti-inflammatory medication colchicine on periprocedural myocardial injury. Methods: Patients undergoing PCI for stable angina or non–ST-segment–elevation myocardial infarction were randomized to oral colchicine (1 mg followed by 0.5 mg 1 hour later) or placebo, 6 to 24 hours preprocedure. Blood samples were taken immediately pre- and 24-hours post-PCI. The primary outcome, periprocedural myocardial infarction, was defined by an increase in post-PCI troponin >5×99th% upper reference limit when the pre-PCI troponin was normal, or >20% increase in post-PCI troponin when the pre-PCI troponin was raised, including supporting evidence of new myocardial ischemia. Major PM-injury was defined as per periprocedural myocardial infarction without supporting evidence of new myocardial ischemia. Minor PM-injury was defined by post-PCI troponin increase >99th% upper reference limit but ≤5×99th% upper reference limit. Results: A total of 196 patients met inclusion criteria and were randomized. One hundred twenty-one patients were excluded (no PCI, unstable troponin before PCI, or poor-quality measurements) leaving a study population of 75 patients. Thirty-six patients were randomized to colchicine and 39 to placebo preprocedure. Forty-four presented with non–ST-segment–elevation myocardial infarction and 31 with stable angina. High-sensitive (hs) troponin-I pre-PCI was similar between treatment groups (colchicine: 79 ng/L [4–1336] versus placebo: 35 [5–448], P =0.42). Absolute change in hs-troponin-I (calculated as 24-hour post-PCI minus pre-PCI measurements) was significantly lower in the colchicine group: 59 (1–221) versus placebo: 166 (53–530), P =0.02. No patients developed periprocedural myocardial infarction in either group. Significantly fewer patients developed major PM-injury: 11 (31%) versus 21 (54%), P =0.04 or minor PM-injury: 21 (58%) versus 33 (85%), P =0.01, if given colchicine pre-PCI. Conclusions: In this randomized pilot trial, colchicine given 6 to 24 hours pre-PCI reduces periprocedural myocardial injury. Registration: URL: https://www.anzctr.org.au ; Unique identifier: ACTRN12615000485538.